PERANAN GURU DALAM MENGEMBANGKAN KEMAMPUAN BERBICARA MELALUI BERCERITA PADA ANAK PAUD TUNAS BANGSA PONTIANAK - Koprita, Yusela; Ali, Muhamad; Lukmanulhakim, Lukmanulhakim (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aimsto determine the role of teachers in developing speaking skills through a method of telling stories to children aged 4-5 yearsin group A in Pontianak tunas bangsa police. Speaking skills have important role in education, both within the family, school and society. The goals to be achieved in developing speaking skills through storytelling methods are to develop language skills, including listening ability, speaking ability and adding vocabulary. In other words to develop basic abilities in early childhood, especially in developing speaking skills in children in group A of North Sumatra Shoots Pontianak. The research method used was descriptive with a qualitative approach. The sample is group A children an teachers. The results of this study are that the teacher has tried his best to develop children’s speaking skills through a method of telling stories so that studentsare able to ad new vocabulary and experience. When the learning process takes place. Based on the results of the study, it was suggested that Tunas Bangsa Pontianak PAUD teachers maintan and improve the teaching method to tell the children to be more enthusiastic and motivated. Keywords: Teacher’s Role, Speech Ability, Storitelling Method